2020
DOI: 10.1177/0194599819901124
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Forearm Free Flap Donor Sites Using Full‐Thickness Skin Grafts Harvested from the Ipsilateral Arm

Abstract: Objective To compare morbidity and aesthetic outcomes of full-thickness skin grafts (FTSGs) and split-thickness skin grafts (STSGs) in the reconstruction of the forearm free flap donor site. Study Design Case series, retrospective chart review. Setting Institutional microvascular database. Subjects and Methods Subjects who underwent forearm free flaps and FTSGs for donor site reconstruction from April 2016 to November 2017 were included. FTSGs were obtained from the donor forearm with a proximal S-shaped incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…These studies favoring STSG were also considerably smaller sample sizes in comparison with others in this review that found FTSG superior. The only study on its own to show significance was Krane et al (2020), which favored FTSG. There was little mention of final aesthetics regarding the donor site for the STSG or FTSG.…”
Section: Resultsmentioning
confidence: 99%
“…These studies favoring STSG were also considerably smaller sample sizes in comparison with others in this review that found FTSG superior. The only study on its own to show significance was Krane et al (2020), which favored FTSG. There was little mention of final aesthetics regarding the donor site for the STSG or FTSG.…”
Section: Resultsmentioning
confidence: 99%
“…Functionally, FTSG has had mixed results when compared to STSG. Some authors have found improved range of wrist motion with FTSG, and others have found the opposite effect [8,20]. FTSG does have the advantage of a closed harvest site with less pain as compared to STSG harvest sites.…”
Section: Full-thickness Skin Graftingmentioning
confidence: 99%
“…RFFF harvest can cause noticeable deficits in hand and arm use including decreased wrist flexion, decreased grip strength, sensory abnormalities, and loss of strength [1][2][3][4][5][6][7]. Additionally, skin graft failure over the donor site can lead to tendon exposure and wound healing delay in anywhere from 5 to 30% of patients [8][9][10]. Aside from being a cosmetic issue, this can lead to decreased hand function due to scarring [9].…”
Section: Introductionmentioning
confidence: 99%
“…The author concluded that contralateral anastomosis is a safe and successful choice in the reconstruction of head and neck defects, particularly with using a radial forearm free flap [1]. Krane et al compared the aesthetic and morbidity results of split-thickness skin grafts and full-thickness skin grafts in the reconstruction of the donor site of the forearm free flap [24]. The author suggested that using full-thickness skin grafts in the reconstruction of the donor site of the forearm free flap would give a better aesthetic outcome without the morbidity of the donor site or wound creation compared to split-thickness skin grafts [24].…”
Section: Complication and Survival Ratementioning
confidence: 99%
“…Krane et al compared the aesthetic and morbidity results of split-thickness skin grafts and full-thickness skin grafts in the reconstruction of the donor site of the forearm free flap [24]. The author suggested that using full-thickness skin grafts in the reconstruction of the donor site of the forearm free flap would give a better aesthetic outcome without the morbidity of the donor site or wound creation compared to split-thickness skin grafts [24]. Gur et al compared current free flap options for intraoral lining and tongue reconstruction.…”
Section: Complication and Survival Ratementioning
confidence: 99%